2008
DOI: 10.1007/s00264-008-0639-3
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and validation of CT scanogram to compare per-operative and post-operative mechanical axis after navigated total knee replacement

Abstract: Our objective was to assess and validate low-dose computed tomography (CT) scanogram as a post-operative imaging modality to measure the mechanical axis after navigated total knee replacement. A prospective study was performed to compare intra-operative and post-operative mechanical axis after navigated total knee replacements. All consecutive patients who underwent navigated total knee replacement between May and December 2006 were included. The intra-operative final axis was recorded, and postoperatively a C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Measurements denoting lateral displacement from the center point of the tibial plateau were ascribed a positive value (+), whereas measurements indicating a medial distance from the center of the tibial plateau were considered negative (À). In this study, the accepted values for normal or in-range alignment were: (1) 2°to 8°valgus for FTA [1,14,25,32,34]; (2) 0°± 3°varus/valgus for HKA [2,3,18,19,23]; and (3) the central zone for ZMA [25,27,30,36]. We determined interrater reliability by calculating the intraclass correlation coefficient (ICC) using a two-way Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Measurements denoting lateral displacement from the center point of the tibial plateau were ascribed a positive value (+), whereas measurements indicating a medial distance from the center of the tibial plateau were considered negative (À). In this study, the accepted values for normal or in-range alignment were: (1) 2°to 8°valgus for FTA [1,14,25,32,34]; (2) 0°± 3°varus/valgus for HKA [2,3,18,19,23]; and (3) the central zone for ZMA [25,27,30,36]. We determined interrater reliability by calculating the intraclass correlation coefficient (ICC) using a two-way Fig.…”
Section: Methodsmentioning
confidence: 99%
“…However, it could be shown that isolated rotation of the leg has no relevant influence on HKA measurements [14]. Furthermore, it could be demonstrated that the use of a CT scanogram for measuring HKA shows reasonable accuracy [22].…”
Section: Discussionmentioning
confidence: 99%
“…). We considered this value (CTV) obtained from the CT scan as the ‘true’ value, as clinically a CT scan can provide a very objective, accurate, and reproducible measure of both rotation and mechanical alignment …”
Section: Methodsmentioning
confidence: 99%
“…We considered this value (CTV) obtained from the CT scan as the 'true' value, as clinically a CT scan can provide a very objective, accurate, and reproducible measure of both rotation 3 and mechanical alignment. 4 We then recruited 31 volunteer orthopaedic surgeons of various levels of experience, including 10 consultants and 21 trainees. The mean number of years of orthopaedic experience was 9.7 ± 7.4 (range 4-34 years).…”
Section: Methodsmentioning
confidence: 99%